ENHANCING GUEST EXPERIENCES THROUGH DIGITAL TECHNOLOGY IN HOSPITALITY - Živkovic, Dragan (The Business of Tourism, 2025)
This study investigates the impact of digital technology on guest experiences in high-category hotels in Serbia, conducted from September to October 2024. A structured questionnaire was utilized, distributed via QR codes to ensure convenience, resulting in 223 valid entries analyzed. Key findings indicate that approximately 78% of respondents perceive digital services positively, with mobile check-in/check-out identified as the most valued feature. Satisfaction levels varied significantly by age, education, and employment status, revealing that younger and more educated guests appreciate digital offerings more. The research contributes to understanding how hotels can tailor their digital services to enhance guest satisfaction and loyalty, emphasizing the necessity for a balanced approach that accommodates diverse guest preferences in an increasingly competitive hospitality market